From Tar City to Smart City: Living with the Smart City Ideology as Senior City Dweller - Suopajärvi, Tiina (Ethnologia Fennica, 2018)
In a smart city, technologies are designed to assist people in their everyday lives, like in intelligent homes, public transportation, and e-services. However, this can lead to new kind of marginalisation if people do not fit into the idea of smart citizen. In this article, I consider how the smart city ideology of Oulu in northern Finland becomes lived in the everyday practices of senior citizens; and how they sense themselves as “smart citizens.” Through generating ethnographic composition of ICT-biography and walk-along interviews, and series of workshops with seniors, city officials and researchers; and thinking this process as collaborative knowledge-making, the configuration of ageing in a smart city has emerged. In this configuration, the city is understood as an assemblage with dynamics of temporalities, structures, communities and individuals; and as part of global power-geometry. Though the seniors support the smart city ideology as regional strategy, they want to make a voluntary decision to become a smart citizen. Current smart city is made for and by technology enthusiasts, and it often excludes other citizens. To become a smart community the city must include variety of citizens in the making of their city. Many seniors are willing to take up this challenge.